Statins and selective inhibition of Rho kinase protect small conductance calcium-activated potassium channel function (K(Ca)2.3) in cerebral arteries. - Alister J McNeish; Francesc Jimenez-Altayo; Graeme S Cottrell; Christopher J Garland (PLoS ONE)
Background In rat middle cerebral and mesenteric arteries the K(Ca)2.3 component of endothelium-dependent hyperpolarization (EDH) is lost following stimulation of thromboxane (TP) receptors, an effect that may contribute to the endothelial dysfunction associated with cardiovascular disease. In cerebral arteries, K(Ca)2.3 loss is associated with NO synthase inhibition, but is restored if TP receptors are blocked. The Rho/Rho kinase pathway is central for TP signalling and statins indirectly inhibit this pathway. The possibility that Rho kinase inhibition and statins sustain K(Ca)2.3 hyperpolarization was investigated in rat middle cerebral arteries (MCA). Methods MCAs were mounted in a wire myograph. The PAR2 agonist, SLIGRL was used to stimulate EDH responses, assessed by simultaneous measurement of smooth muscle membrane potential and tension. TP expression was assessed with rt-PCR and immunofluorescence. Results Immunofluorescence detected TP in the endothelial cell layer of MCA. Vasoconstriction to the TP agonist, U46619 was reduced by Rho kinase inhibition. TP receptor stimulation lead to loss of K(Ca)2.3 mediated hyperpolarization, an effect that was reversed by Rho kinase inhibitors or simvastatin. K(Ca)2.3 activity was lost in L-NAME-treated arteries, but was restored by Rho kinase inhibition or statin treatment. The restorative effect of simvastatin was blocked after incubation with geranylgeranyl-pyrophosphate to circumvent loss of isoprenylation. Conclusions Rho/Rho kinase signalling following TP stimulation and L-NAME regulates endothelial cell K(Ca)2.3 function. The ability of statins to prevent isoprenylation and perhaps inhibit of Rho restores/protects the input of K(Ca)2.3 to EDH in the MCA, and represents a beneficial pleiotropic effect of statin treatment.